2015
DOI: 10.1626/pps.18.218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Fertilizer and Planting Density on the Lignin Synthesis in the Culm in Relation to Lodging Resistance of Buckwheat

Abstract: Lodging is an important constraint limiting buckwheat yield and quality by bending or breaking culm on buckwheat production worldwide. This study was conducted with Ningqiao 01, a moderate lodging resistance cultivar of buckwheat, to determine whether lignin synthesis and lodging resistance of buckwheat are affected by nitrogen fertilizer and planting density. The results showed that the lignin content at the bottom of the 2nd internode was significantly and negatively correlated with lodging index and lodging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 32 publications
7
44
0
1
Order By: Relevance
“…Various workers also reported that lignin is an important factor for lodging resistance of wheat (Berry & Spink, ; Ma, ; Peng et al., ), rice (Ookawa & Ishihara, , ) and Arabidopsis (Jones, Ennos, & Turner, ). In the present study, our results suggested that the lignin accumulation is closely related to the lodging resistance of common buckwheat, and higher lignin accumulation could strengthen the lodging‐resistant ability of common buckwheat, which was consistent with the previous study (Wang, Hu, et al., ; Wang, Ruan, et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Various workers also reported that lignin is an important factor for lodging resistance of wheat (Berry & Spink, ; Ma, ; Peng et al., ), rice (Ookawa & Ishihara, , ) and Arabidopsis (Jones, Ennos, & Turner, ). In the present study, our results suggested that the lignin accumulation is closely related to the lodging resistance of common buckwheat, and higher lignin accumulation could strengthen the lodging‐resistant ability of common buckwheat, which was consistent with the previous study (Wang, Hu, et al., ; Wang, Ruan, et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…It was also reported that the lignin content and its related enzymes activities were significantly related to lodging resistance of culm in common buckwheat and buckwheat cultivars with high lodging resistance usually have large culm quality and short second internode length (Wang, et al. ; Wang, Hu, et al., ; Wang, Ruan, et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations